Development of Artificial Intelligence in the Dispute Resolution of Religious Courts - Imaro Sidqi; Siti Maymanatun Nisa; Hening Sukma Daini (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The number of disputes in religious courts continues to increase every year, giving great potential to develop the use of artificial intelligence to make it more efficient and effective by paying attention to the basic principles of Islamic law. This paper discusses the potential and development of the use of artificial intelligence technology in dispute cases in religious courts based on Maslahah Mursalah. The research method is juridical-normative, with a conceptual and philosophical approach. The research shows that the use of artificial intelligence in dispute resolution at religious courts is important for the reason that it can minimize the risk of errors and help judges determine legal considerations in the dispute resolution of Islamic law so that they are more accurate, effective, and efficient. The potential for developing the use of artificial intelligence technology in religious courts must consider several aspects, including the integration of artificial intelligence technology in the dispute resolution process in religious courts, the development of artificial intelligence-based decision support systems, and legal-ethical aspects of the use of artificial intelligence in religious courts. The formulation of the concept for developing the use of artificial intelligence technology in dispute resolution in the religious courts must be guided by the Maslahah Mursalah principle as a moral-ethical foundation within the legal system framework, which includes legal structure, legal substance, and legal culture so that the development of the use of artificial intelligence technology in the disputes resolution of Islamic law in religious courts be effective and justice for all.